Comparative efficacy of intrastromal amphotericin B versus voriconazole in treating deep-stromal refractory fungal keratitis - Charul Singh; Amrita Mohanty; Raksheeth N Rajagopal; Md Hasnat Ali; Joveeta Joseph; Bhupesh Bagga (Indian Journal of Ophthalmology, 2025)
Purpose: To compare the outcome of adjuvant intrastromal Amphotericin B (ISAMPB) and Voriconazole (ISVCZ) in managing refractory deep stromal fungal keratitis. Methods: We reviewed the records of patients treated between January 2020 and December 2022 for microbiologically confirmed refractory fungal keratitis that had worsened despite treatment with topical Natamycin, with or without oral Ketoconazole. These patients received adjuvant therapy with either intrastromal Amphotericin B (ISAMPB, 5–10 µg/0.1 ml) or intrastromal Voriconazole (ISVCZ, 50 µg/0.1 ml). The demographics, clinical profiles, and outcomes of the ISAMPB and ISVCZ groups were compared, with key outcomes being the proportion of patients achieving clinical resolution and the number of therapeutic keratoplasty procedures performed. A logistic regression model was constructed for multivariate analysis to adjust for potential confounders. Results: Medical records of 49 patients with refractory fungal keratitis were analyzed: 34 (69.3%) received ISAMPB, and 15 (30.6%) received ISVCZ. The overall mean LogMAR visual acuity was 1.90 ± 0.6, and the infiltrate size averaged 4.28 ± 1.30 mm vertically and 4.3 ± 1.4 mm horizontally. Aspergillus and Fusarium each accounted for 32.3% of ISAMPB patients, and 40% and 20% of ISVCZ patients, respectively. The median time to intrastromal injection was 12 days for ISAMPB and 11 days for ISVCZ. ISAMPB achieved resolution in 53% of cases, while 41.1% required TPK; ISVCZ resolved in 10%, with 86% requiring TPK (P < 0.01). The adjusted odds ratio for ISAMPB response was 21.98 (P = 0.013). Conclusion: Intrastromal Amphotericin B has been shown to provide better outcomes than Voriconazole in the treatment of deep stromal refractory fungal keratitis.